Konstruksi Gender dan Kebijakan Mitigasi Bencana pada Pekerja Perkebunan Kopi di Lereng Gunung Argopuro - M Khoirul Hadi al Asy Ari; Agustin Lisnawati; Rifka Herliani (AN-NISA, 2019)
Gender Construction and Disaster Mitigation Policy for Coffee Plantation Workers on the Argopuro Mountain SlopeThis article aims to understand how gender construction and disaster mitigation policy for coffee plantation workers on the mountain slopes of Argopuro. In this article there are three focus questions: First, what is the gender construction of coffee plantation workers? Second, how is disaster mitigation management based on coffee plantation workers? Third, how is the construction of gender-based disaster mitigation management policies for coffee plantation workers? This article uses a descriptive exploratory method with a sociological approach. For answering those three focus questions in this article, it is using the perspective of Peter Berger's social construction, where there are three dialectical phases in the process of interpreting individuals with their social world, namely internalization, objectivation and externalization. The objectivation and internalization phase are the process of understanding the workers regarding the management of gender-based disaster mitigation policies. The objectivation and externalization phase are processes of assessing the management of gender-based disaster mitigation policies. It can be concluded that the involvement of women in work activities has shown a form of gender responsiveness, but in disaster mitigation policy management has not been gender responsive.AbstrakArtikel ini bertujuan untuk memahami bagaimana konstruksi gender dan kebijakan mitigasi bencana bagi para pekerja perkebunan kopi di lereng gunung argopuro. Dalam artikel ini ada tiga fokus pertanyaan, Pertama, bagaimana konstruksi gender pekerja perkebunan kopi? Kedua, bagaimana manajemen mitigasi bencana berbasis pekerja perkebunan kopi? Ketiga, bagaimana konstruksi gender berbasis manajemen kebijakan mitigasi bencana bagi pekerja perkebunan kopi? Artikel ini menggunakan metode deskriptif eksploratif dengan pendekatan sosiologis. Adapun untuk menjawab tiga fokus pertanyaan dalam artikel ini, menggunakan perspektif konstruksi sosial peter berger, di mana ada tiga fase dialektis dalam proses pemaknaan individu dengan dunia sosialnya yaitu internalisasi, objektivasi dan eksternalisasi. Fase objektivasi dan internalisasi merupakan proses pemahaman para pekerja mengenai manajemen kebijakan mitigasi bencana berbasis gender. Fase objektivasi dan eksternalisasi merupakan proses menilai manajemen kebijakan mitigasi bencana berbasis gender. Dapat disimpulkan bahwa terlibatnya perempuan dalam aktivitas kerja sudah menunjukkan bentuk responsif gender, tetapi dalam manajemen kebijakan mitigasi bencana belum responsif gender.